The Role of Law-Consciousness in the Development of the Ancient Society - Šerpytytė, Rita (Problemos, 1987)
From the Marxist point of view the role of law-consciousness in the development of society is determined by the specific practical prerequisites. The latter lead to the alienation of social relations and thus produce the necessity of their regulation. An attempt is made to disclose the way in which the alienation is fixed in the theoretical concepts of “right”, “law”, and “justice”. The conceptions of right by Plato, Aristotle and the Stoics are considered.